Endeavoring to Contextualize Curricula Within an EBP Framework: A Grounded Theory Study. (December 2018) - Malik, Gulzar; McKenna, Lisa; Griffiths, Debra
Adopting evidence-based practice (EBP) principles in undergraduate education can facilitate nursing students' appreciation of EBP. Using grounded theory method, this study aimed to explore processes used by nurse academics while integrating EBP concepts in undergraduate nursing curricula across Australian universities. Twenty-three nurse academics were interviewed and nine were observed during teaching of undergraduate students. In addition, 20 unit/subject guides were analyzed using grounded theory approach of data analysis. The theory " On a path to success: Endeavoring to contextualize curricula within an EBP framework " reflects academics' endeavors toward linking EBP concepts to practice, aiming to contextualize curricula in a manner that engages students within an EBP framework. However, academics' journeys were influenced by several contextual factors which require strategies to accomplish their endeavors. In conclusion, initiatives to minimize barriers, faculty development, and provision of resources across educational and clinical settings are fundamental to achieving undergraduate curricula underpinned by EBP concepts.